The effect of biogenic selenium nanoparticles (Cissus quadrangularis) on the performance and antioxidant status of piglet in the climatic conditions of Zambia - Chilala, Pompido; Skalickova, Sylvie; Horky, Pavel (Frontiers in Veterinary Science, 2026)
Thermal stress limits sustainable pig production in tropical regions by impairing growth, feed efficiency, and welfare. This study evaluated dietary Cissus quadrangularis selenium nanoparticles (CQ-SeNPs) for supporting growth performance and antioxidant capacity in pigs under natural tropical conditions in Zambia. Thirty-three weaner pigs were randomly assigned to three diets: control (basal), inorganic selenium (Na₂SeO₃), or CQ-SeNPs, and monitored for 30 days under moderate ambient temperatures below heat stress thresholds (27–32 °C for lighter and 18–28 °C for heavier piglets). Growth performance, including body weight, average daily gain (ADG), and feed conversion ratio (FCR), was measured. CQ-SeNPs supplemented pigs showed numerically higher ADG (267 g/day) and lower FCR (1.98) compared with control (264 g/day, 1.99) and Na₂SeO₃ (253 g/day, 2.04), but differences were not statistically significant (p > 0.05). Body weight trends were similar across treatments, indicating limited activation of stress-related physiological pathways under these conditions. These results indicate that CQ-SeNPs supplementation is safe and may support growth under oxidative or thermal challenge, though further studies under defined heat stress are needed to confirm efficacy. Overall, findings highlight the potential of phytogenic selenium nanoparticles in developing climate-adaptive feeding strategies for sustainable swine production in tropical regions.